Enhancing Students’ Critical Reading Skills through Global News Analysis Model (GNAM) in English for International Relations Contexts - Akhmad Heriyadi; Dedi Rahman Nur; Abdul Rohman; Sukaena Sukaena; Shorea Helminasari; Annisa Rohmah; Yasmin Auliasari; Indah Farma Pasaribu; Maria Goretti Adella Kornelia Yulianti Hiping (Borneo Educational Journal (Borju), 2026)
Critical reading is a core academic competence for International Relations students who regularly engage with global news texts. Such texts frequently embed ideological framing, selective evidence, and political agendas that require analytical interpretation. This study examines students’ self-perceived critical reading competence after instruction using the Global News Analysis Model (GNAM). It also explores students’ perceptions of GNAM’s effectiveness and identifies instructional components perceived as most influential. A quantitative descriptive survey was conducted with 72 International Relations students who completed GNAM-based learning activities. Data were collected using a validated questionnaire with a five-point Likert scale. Reliability analysis showed strong internal consistency (Cronbach’s Alpha = 0.88). Results indicate moderate to high perceived critical reading competence, with the strongest confidence in identifying main claims (M = 4.12, SD = 0.54) and the weakest in detecting media bias and framing (M = 3.31, SD = 0.73). GNAM was perceived as effective overall (M = 4.07, SD = 0.45), particularly in comparative media analysis (M = 4.26, SD = 0.49). The findings suggest that GNAM supports students’ analytical awareness of global news, although deeper ideological evaluation remains challenging.